Efficient modeling of entangled details for natural scenes - Guérin, Eric; Galin, Eric; Grosbellet, François; Peytavie, Adrien; Génevaux, Jean-David (Computer graphics forum, 2016)
Digital landscape realism often comes from the multitude of details that are hard to model such as fallen leaves, rock piles or entangled fallen branches. In this article, we present a method for augmenting natural scenes with a huge amount of details such as grass tufts, stones, leaves or twigs. Our approach takes advantage of the observation that those details can be approximated by replications of a few similar objects and therefore relies on mass‐instancing. We propose an original structure, the Ghost Tile, that stores a huge number of overlapping candidate objects in a tile, along with a pre‐computed collision graph. Details are created by traversing the scene with the Ghost Tile and generating instances according to user‐defined density fields that allow to sculpt layers and piles of entangled objects while providing control over their density and distribution.